HUBUNGAN SKALA NYERI PENDERITA TENSION TYPE HEADACHE DENGAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UMSU 2016 - NABILA ULYA; ANITA SURYA (LP2MTBM MAKARIOZ, 2021)
Tension Type Headache (TTH) is the third most frequent disease after dental caries and TB infections. The severity of painin TTH sufferers with a history of poor quality sleep compared, in those with better sleep quality so that, it becomes a riskfactor. This study aims to determine the relationship pain scale patients tension type headache with sleep quality in theFaculty of Medicine UMSU 2016. This research is observational analytic with cross sectional design and total sampling.Ninetyone Patients TTH among 50 people (54.9%) them have poor sleep quality and moderate pain with the amount of 54people (59.3%). analysis of data obtained P-value relationship between the pain scale and sleep quality of 0.000 (P < 0.05).it means that there was a significant relationship between the pain scales of headache tension type with sleep quality.Increased pain scale in patients with TTH had an impact on the worsening sleep quality.